The MacBride Report - 25 years later - Osolnik, Bogdan (Javnost (Ljubljana), 2005)
The MacBride Report initiated a wide international debate not only within the professional circles but also amongst the broader public. This debate provoked a major political and ideological confrontation in which the opponents of the Report's orientation endeavoured to disqualify the entire Report and particularly so its recommendations. Consequently, the entire work of UNESCO in the field of information and communication was heavily criticised and obstructed. The Introduction presents an insight into the work of the Commission by one of its active members, and key recommendations proposed by the MacBride Commission for future activities in the field of information and communication.
Keywords: informacije; informacijska tehnologija; information technology; telecommunication; telekomunikacije; communication; komuniciranje; sociologija komunikacij